Influencia de la presencia de S sobre vainas de Zry-4 - Leyva, Gabriela; Bordoni, Roberto Antonio; Markiewitcz, Mario E.; Geldstein, María C.; Marajofsky, Adolfo; Celora de Lavagnino, Julia; Vidal, D. O.; Recalde, R. L.; Giorgis, N. (Asociación Argentina de Tecnología Nuclear (AATN), 1984)
Fil: Leyva, Gabriela Comisión Nacional de Energía Atómica; Argentina